(untitled) (Fractal: Journal of Psychology, 2009)
From the documentary Paulinho da Viola: meu tempo é hoje (Paulinho da Viola: my time is today), I aim at problematizing the hegemonic politics at the present time which has oriented the subjectivity in the cultural capitalism context. In the documentary, what draws my attention is the way the composer treats time and puts in jeopardy the predominant forms of experimenting it - captured in a longing past and badly lived or in a cynical present, frozen and indifferent to the body’s restlessness. The movie leads me to glimpse the resistance lines and the subjectivity invention; resistance to the hegemonic politics of the present time and invention of new temporalities, vital potencies in extreme acceleration contexts and subtle life controls.